Meshless Fragile Points Method (FPM) in a 2D and 3D potential compressible subsonic fluid flow - Grujičić, Rade; Mladenović, Nikola; Bengin, Aleksandar; Vorotović, Goran; Dong, Leiting; Atluri, Satya N. (Engineering analysis with boundary elements, 2023)
The possibility of the implementation of Fragile Points Method (FPM) in the analysis and solving of the fluid flow problems is demonstrated in this paper. Subject of interest was the compressible potential flow equation, which was discretised by using the meshless Galerkin FPM. Discontinuous and point-based trial and test functions were used, with the introduction of Numerical Flux Corrections for overcoming the inaccuracy and instability side-effects brought by discontinuities. By comparison with the analytical, experimental and numerical results available in literature, FPM was verified, and it was shown that FPM could be very good tool for the potential compressible fluid flow simulations.